KECANTIKAN DAN DIALEKTIKA IDENTITAS TUBUH PEREMPUAN PASCAKOLONIAL DALAM CERITA PENDEK CHINA DOLLS DAN WHEN ASIAN EYES ARE SMILING - Setyorini, Ari (Jurnal Ilmiah Lingua Idea, 2016)
Beauty concept, as one of the central features of women’s oppression, has been standardized by the West through their global culture machine time after time. By contrasting a bold binary opposition between the West female body and the Other’s female body, the West has classified some certain features for shaping the construction of beauty concept. The binary causes the in-between feeling as described by Alaina Wong and Lois Ann Yamanaka in their short stories entitled China Doll (2001) and When Asian Eyes are Smiling (2001). The short stories show how the female characters of short stories, who are represented the Asian American women, are being colonized through some stereotypes since their body contours do not meet the standard of a beautiful body. Despite the stereotypes that embedded to the Asian American women; in fact, they are able to redefine the meaning of beauty through some cultural strategies. Thus, this study aims at knowing how Asian American women reconstruct their conceptual understanding of body and beauty which has been imposed by the West. By reshaping their body contours or even imitating the West beauty treatments, Asian American women are disrupting the essential concept of the so-called a beautiful body